2011
DOI: 10.1097/nmd.0b013e318221413e
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and Global Assessment of Functioning in Male and Female Outpatients With Schizophrenia Spectrum Disorders

Abstract: The relationship between the symptom and function subscales of the Global Assessment of Functioning (GAF) and neurocognitive test performance was studied in 195 outpatients with schizophrenia, schizoaffective disorder, or delusional disorder who were assigned to functional groups based on their sex. A composite cognition score was created based on z-scores. Stepwise multiple regression analysis was used to assess the predictive value of GAF Symptom and GAF Function on composite cognition and to check for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 26 publications
2
13
1
1
Order By: Relevance
“…A recent meta-analysis examining cognition in first-episode psychosis concluded that the degree of cognitive change over time tends to be similar in cases and controls (Bozikas and Andreou, 2011). Although other studies have shown an association between cognition and indexes of everyday functioning (Green et al, 2000, 2004, 2006), including the Global Assessment of Functioning (GAF; Karilampi et al, 2011), we found no significant association between patient GAF scores and cognitive ability. This null finding may reflect the relatively small number of studies reporting GAF data in our sample (K = 11) or the mixture of symptom severity with everyday functioning in GAF ratings.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent meta-analysis examining cognition in first-episode psychosis concluded that the degree of cognitive change over time tends to be similar in cases and controls (Bozikas and Andreou, 2011). Although other studies have shown an association between cognition and indexes of everyday functioning (Green et al, 2000, 2004, 2006), including the Global Assessment of Functioning (GAF; Karilampi et al, 2011), we found no significant association between patient GAF scores and cognitive ability. This null finding may reflect the relatively small number of studies reporting GAF data in our sample (K = 11) or the mixture of symptom severity with everyday functioning in GAF ratings.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are comparable to the scores found in other studies that have used the GAF to assess functioning in schizophrenia patients 56,57 . As has been previously described in schizophrenia 12,13 the mean scores of our patient sample for all MCCB cognitive domains were between one and two standard deviations below the population mean (T = 50).…”
Section: Discussionsupporting
confidence: 79%
“…In the study by Karilampi et al [59], better cognitive function was predicted by higher psychosocial functioning levels in males but by lower symptom levels in females, suggesting a slight difference between women and men in the domains relating to cognitive function, which need to be taken into account.…”
Section: Cognitive Functioningmentioning
confidence: 99%